2014
DOI: 10.1116/1.4875935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postdeposition annealing on the electrical properties of β-Ga2O3 thin films grown on p-Si by plasma-enhanced atomic layer deposition

Abstract: Ga2O3 dielectric thin films were deposited on (111)-oriented p-type silicon wafers by plasma-enhanced atomic layer deposition using trimethylgallium and oxygen plasma. Structural analysis of the Ga2O3 thin films was carried out using grazing-incidence x-ray diffraction. As-deposited films were amorphous. Upon postdeposition annealing at 700, 800, and 900 °C for 30 min under N2 ambient, films crystallized into β-form monoclinic structure. Electrical properties of the β-Ga2O3 thin films were then investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
(46 reference statements)
2
28
0
Order By: Relevance
“…, . Indeed, the values (and polarity) of the charge reported in this study for the Ga 2 O 3 –Si interface are similar to those recently reported by Altuntas et al for crystalline (β‐phase) Ga 2 O 3 on silicon formed by annealing PE‐ALD films at elevated temperatures (≥700 °C), though the authors in that study were unable to obtain CV data for un‐annealed, amorphous Ga 2 O 3 –Si structures .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…, . Indeed, the values (and polarity) of the charge reported in this study for the Ga 2 O 3 –Si interface are similar to those recently reported by Altuntas et al for crystalline (β‐phase) Ga 2 O 3 on silicon formed by annealing PE‐ALD films at elevated temperatures (≥700 °C), though the authors in that study were unable to obtain CV data for un‐annealed, amorphous Ga 2 O 3 –Si structures .…”
Section: Resultssupporting
confidence: 90%
“…Carbon contamination is common for Al 2 O 3 ALD films, and is a remanent from the organic methyl (CH 3 ) ligands common to the trimethyl‐aluminium and trimethyl‐gallium precursors . Altuntas et al also report negligible residual carbon in similarly prepared PE‐ALD Ga 2 O 3 films, as determined by sputter depth profilometry . A small, broad feature in the pre‐annealed sample in the range 2600 cm –1 to 3700 cm –1 (band (d) in the figure) indicates the possible incorporation of hydrogen in the film, in the form of O–H bonds .…”
Section: Resultsmentioning
confidence: 88%
“…We controlled the ALD process circle to manufacture different dielectric thicknesses. A post-deposition annealing (PDA) process was applied to increase the quality of the oxide-semiconductor interface [14][15][16][17]. The process involved heating the film from ambient temperature to 380 • C in N 2 over 15 s, annealing for 60 s , and then cooling to ambient temperature over 300 s [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] With a wide bandgap of ≈4.7–4.9 eV and excellent chemical and physical stability, gallium oxide (Ga 2 O 3 ) has become an attractive choice of material for UV‐C photodetectors (PDs). [ 2 ] The unique combination of high bandgap and ability to extrinsically n ‐type‐doped Ga 2 O 3 has led to a measurable interest in studying a wide range of prospective heterostructure combinations, such as MgZnO/Ga 2 O 3 , [ 3 ] Ga 2 O 3 /GaN, [ 4 ] Ga 2 O 3 /SiC, [ 5 ] and Ga 2 O 3 /Si, [ 6–14 ] for use as UV PDs. Among these heterojunctions, Ga 2 O 3 /Si is especially attractive due to the well‐known cost and availability advantages of Si substrates, and its prominent applications in Si‐based optoelectronic integrated circuits.…”
Section: Introductionmentioning
confidence: 99%
“…n ‐type β‐Ga 2 O 3 nanobelts contacted onto p ‐Si substrate have also been explored for UV‐C PDs. [ 10 ] Amorphous Ga 2 O 3 ‐based PDs have also been demonstrated on silicon substrates using atomic layer deposition (ALD) [ 11,12,14 ] and metal–organic chemical vapor deposition (MOCVD). [ 15 ]…”
Section: Introductionmentioning
confidence: 99%